Effects of porcine circovirus type 2 and mycoplasma hyopneumoniae vaccination strategy, birth weight, and gender on postweaning performance of growing-finishing pigs reared in a commercial environment - Bergstrom, J. R.; Potter, M. L.; Henry, Steven C.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,995 pigs were used to evaluate the effects of two porcine circovirus type 2 (PCV2) and Mycoplasma hyopneumoniae (Mhyo) vaccination strategies and birth weight on pig performance and carcass characteristics. The first vaccination strategy (BI) was a single full dose of CircoFLEX-MycoFLEX (Boehringer Ingelheim, St. Joseph, MO) at weaning. The second strategy (Intervet) was a full dose of Circumvent and MYCOSILENCER (Intervet/Schering-Plough Animal Health, Millsboro, DE) at weaning and again 22 d later. At a commercial sow farm, all pigs born alive for 22 consecutive days were identified individually at birth with a numbered ear tag. The dam, gender, and birth weight were recorded and used to randomly allot pigs at weaning (d 0) to the PCV2/Mhyo vaccination treatments. The pigs were weaned into 4 consecutive nursery rooms of approximately 500 pigs each on 6 occasions during a 19-d period. Pigs from each vaccination treatment were comingled in pens within rooms throughout the study. Pigs were moved to a finishing barn on d 74. Pigs were individually weighed on d 0, 22, 44, 74, and 156 to measure growth rate. Carcass data were obtained from a subsample of 420 pigs harvested on a single day (d 167). For data analysis, individual birth weight was used to assign pigs to 7 birth weight categories, each containing a similar number of observations. Therefore, data were analyzed as a 2 × 2 × 7 factorial arrangement in a completely randomized design with main effects of vaccine strategy, gender, and weight category. As birth weight category increased, ADG increased (P < 0.01) during each weight period and overall. Percentage of culls and light weight pigs at market also were reduced (P < 0.01) as weight category increased. Overall, ADG, final BW, HCW, and backfat depth of barrows were increased (P < 0.0001) compared with gilts, whereas the percentage of culls and pigs < 215 lb and fat-free lean were reduced (P < 0.0001) compared with gilts. From d 0 to 22 and d 44 to 74, vaccine strategy did not influence ADG. However, ADG and BW were greater (P < 0.05) from d 22 to 44 for pigs vaccinated once with BI rather than twice with Intervet. From d 74 to 156, pigs vaccinated twice with Intervet had greater (P < 0.05) ADG than those vaccinated once with BI. Thus, there were no differences between the 2 vaccination strategies for overall growth performance, carcass measurements, or mortality. These results are similar to those of previous experiments that demonstrated that vaccination with Intervet reduced performance in the nursery stage but improved performance in the finisher stage. In summary, vaccination strategy, piglet birth weight, and gender all influence the growth of pigs during the nursery stage, finishing stage, and overall and should be considered to enhance overall performance.
Keywords: Birth weight; Gender; Growth; PCV2; Vaccination; Swine